2020
DOI: 10.3390/antiox9040332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin on the Renal Toxicity Induced by Ochratoxin A in Rats

Abstract: Ochratoxin A (OTA) is a powerful nephrotoxin and the severity of its damage to kidneys depends on both the dose and duration of exposure. According to the scientific data currently available, the mechanism of action still is not completely clarified, but it is supposed that oxidative stress is responsible for OTA-induced nephrotoxicity. Bioactive compound use has emerged as a potential approach to reduce chronic renal failure. Therefore, curcumin (CURC), due to its therapeutic effects, has been chosen for our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
(58 reference statements)
3
28
0
Order By: Relevance
“…The liver is constantly negatively affected by various xenobiotics and free radicals, as it is the organ in charge of biotransformation processes. In fact, several studies reported CURC as a scavenger for the oxygen-derived free radicals [ 34 , 57 ]. In this study, we analyzed the main serum biomarkers essential for the determination of liver injury [ 58 , 59 ], and we found, in rats treated with OTA for 14 days, a significant increase in serum aminotransferases (ALT and AST) and ALP that suggests damage to the liver cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The liver is constantly negatively affected by various xenobiotics and free radicals, as it is the organ in charge of biotransformation processes. In fact, several studies reported CURC as a scavenger for the oxygen-derived free radicals [ 34 , 57 ]. In this study, we analyzed the main serum biomarkers essential for the determination of liver injury [ 58 , 59 ], and we found, in rats treated with OTA for 14 days, a significant increase in serum aminotransferases (ALT and AST) and ALP that suggests damage to the liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…This study, according to the studies of Emad et al [ 59 ] and Omowumi et al [ 60 ], allows us to hypothesize that CURC increases protein synthesis in liver cells damaged by OTA for a regenerative effect on liver tissue. Mycotoxins cause the release of free radicals, induce lipid peroxidation, and change the antioxidant status of cells, leading to oxidative stress [ 34 , 61 ]. Therefore, in this study, we have evaluated the activity of the main antioxidant enzymes, namely CAT, SOD, and GPx, which play a key role in protecting against oxidative stress induced by reactive oxygen species [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OTA has various possible targets such as the liver, immune system, heart and brain; however, owing to the function of the organ, its main target is the kidneys [ 10 , 11 , 12 ]. The kidneys balance the metabolism of salt and water, regulate the levels of electrolytes in blood, and play several important physiological roles including maintaining the stable composition of blood and secretion of hormones [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excretory function, the kidney is threatened by a variety of harmful substances such as drugs or food contaminants, like mycotoxins leading to acute or—even worse—chronic kidney diseases with a prevalence of about 10% [ 1 , 2 ]. To understand the mechanisms of the nephrotoxic action it is helpful to find strategies to alleviate these detrimental scenarios and many studies have been performed to solve the question of why and how kidneys are endangered [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%